BROAD Group : Chinese innovation in the air - Williamson, Peter J. (SAGE knowledge. Cases., 2016)
This case explores how the Chinese company, BROAD Group, innovated by taking an existing technology (non-electric air conditioning) and re-engineering it to dramatically improve the energy efficiency and reduce the environmental impact of large-scale air conditioning systems used in applications as diverse as skyscrapers and airports.